2019
DOI: 10.17576/jem-2019-5303-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Credit Market in Indonesian Banking Industry

Abstract: This study aims to find out determinants of conventional banks' credit supply and demand in Indonesia between 2005 and 2014, a period after recovery from financial crisis in 1997/1998. Some literatures suggest that demand and supply of credit are determined by the rates of credit and bonds. This study contribute to the literature by considering the role of prudential policy, market structure and banks ownership on supply and demand for credits. By using the bank level yearly data, the Seemingly Unrelated Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For example, Huang (2010) argued that the influence of the legal and regulatory environment was vital for the financial system, and the appropriate enforcement of contract and property rights facilitated bank lending. Similarly, Hasan (2011) and Rahayu et al (2019) further showed that regulatory system enforcement improved contract efficiency, accounting information disclosure and acceptable bank practices, which supported financial system development. Barth et al (2004) noted that restrictions on the activities of financial institutions could be detrimental to bank performance and increase banking failures.…”
Section: Literature Reviewmentioning
confidence: 77%
“…For example, Huang (2010) argued that the influence of the legal and regulatory environment was vital for the financial system, and the appropriate enforcement of contract and property rights facilitated bank lending. Similarly, Hasan (2011) and Rahayu et al (2019) further showed that regulatory system enforcement improved contract efficiency, accounting information disclosure and acceptable bank practices, which supported financial system development. Barth et al (2004) noted that restrictions on the activities of financial institutions could be detrimental to bank performance and increase banking failures.…”
Section: Literature Reviewmentioning
confidence: 77%